2019
DOI: 10.1002/jbio.201800343
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐wavelength light emitting diode‐based disposable optrode array for in vivo optogenetic modulation

Abstract: We present a light emitting diode (LED)‐based optical waveguide array that can optogenetically modulate genetically targeted neurons in the brain. The reusable part of the system consists of control electronics and conventional multi‐wavelength LED. The disposable part comprises optical fibers assembled with microlens array fabricated on a silicon die. Both parts can be easily assembled and separated by snap fit structure. Measured light intensity is 3.35 mW/mm2 at 469 nm and 0.29 mW/mm2 at 590 nm when the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Coupling of a single LED into multiple fibers has also been tested, giving multisite illumination, but without individual control of illumination sites. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Coupling of a single LED into multiple fibers has also been tested, giving multisite illumination, but without individual control of illumination sites. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The utility of the optical system was verified in previous studies in terms of light intensity, heat dissipation, and spatial light distribution [21,25]. In this study, a new optrode array integrated with electrophysiological recording electrodes was proposed so that the neural activity from adjacent neurons evoked by optogenetic stimulation could be recorded.…”
Section: Introductionmentioning
confidence: 71%
“…When the LED is turned on, the light passes through the MLA and the optical fiber array and reaches the fiber tip to illuminate the target region. In the previous study, it was shown that the temperature increase at the optical fiber tip was less than 0.5 • C, and the relative light intensity remained above 91% up to a distance of 2 mm from the tip [21]. The excitation parameters can be controlled by changing the frequency, pulse width, application time, and input current using the external power supply.…”
Section: Mems Optrode Array Assemblymentioning
confidence: 99%
See 2 more Smart Citations